Complete chloroplast genome sequences of Myristicaceae species with the comparative chloroplast genomics and phylogenetic relationships among them - Mao, Changli; Zhang, Fengliang; Li, Xiaoqin; Yang, Tian; Zhao, Qi; Wu, Yu (PloS one, 2023)
Myristicaceae was widly distributed from tropical Asia to Oceania, Africa, and tropical America. There are 3 genera and 10 species of Myristicaceae present in China, mainly distributed in the south of Yunnan Province. Most research on this family focuses on fatty acids, medicine, and morphology. Based on the morphology, fatty acid chemotaxonomy, and a few of molecular data, the phylogenetic position of Horsfieldia pandurifolia Hu was controversial. In this study, the chloroplast genomes of two Knema species, Knema globularia (Lam.) Warb. and Knema cinerea (Poir.) Warb., were characterized. Comparing the genome structure of these two species with those of other eight published species, including three Horsfieldia species, four Knema species, and one Myristica species, it was found that the chloroplast genomes of these species were relatively conserved, retaining the same gene order. Through sequence divergence analysis, there were 11 genes and 18 intergenic spacers were subject to positive selection, which can be used to analyze the population genetic structure of this family. Phylogenetic analysis showed that all Knema species were clustered in the same group and formed a sister clade with Myristica species support by both high maximum likelihood bootstrap values and Bayesian posterior probabilities; among Horsfieldia species, Horsfieldia amygdalina (Wall.) Warb., Horsfieldia kingii (Hook.f.) Warb., Horsfieldia hainanensis Merr. and Horsfieldia tetratepala C.Y.Wu. were grouped together, but H. pandurifolia formed a single group and formed a sister clade with genus Myristica and Knema. Through the phylogenetic analysis, we support de Wilde' view that the H. pandurifolia should be separated from Horsfieldia and placed in the genus Endocomia, namely Endocomia macrocoma subsp. prainii (King) W.J.de Wilde. The findings of this study provide a novel genetic resources for future research in Myristicaceae and provide a molecular evidence for the taxonomic classification of Myristicaceae.